Chlorine Effects of Heterocyclic Ring‐Based Donor Polymer for Low‐Cost and High‐Performance Nonfullerene Polymer Solar Cells. Issue 7 (2nd July 2019) - Jeon, Sung Jae; Han, Yong Woon; Moon, Doo Kyung
Abstract : In article no.1900094, Doo Kyung Moon and co‐workers newly synthesize a chlorinated thiophenebased donor polymer, P(Cl), which has a relatively low synthetic complexity. P(Cl) shows an excellent power conversion efficiency and high atmospheric stability in non‐fullerene polymer solar cells.